Substitution of Lindur Fruits Flour on the preferences level of Catfish Meatballs - Muammar Alno; Nia Kurniawati; Evi Liviawaty (Jurnal Perikanan dan Kelautan, 2018)
Catfish (Clarias gariepinus) in addition to containing essential  nutrients such as protein also contain essential amino acids. If compared with red meat such as beef and chicken,nutritional content catfish more healthy because of high protein also low in fat and cholesterol. To reduce the price of high import tapioca, lindur flesh can be used as flour for one alternative in tapioca starch ingredients in fishballs. Lindur fruit is one  typeof mangrove that is very potential as a new food source because of its high protein and carbohydrate content. The purpose of this research was determine the number of substitution of the best lindur flour to the level of preference catfishballs. This research was conducted in May 2017. Located at the Fishery Product Laboratory Faculty of Fisheries and Marine Science Padjadjaran University and Proximate Test was conducted at the Food Technology Laboratory Faculty of Technique Pasundan University. The method used was experimental, with 20 semi-trained panelists with five treatments substitution of tapioca and lindur flour which are 0%:100%, 12.5%:87.5%, 25%:75%, 37.5%:62.5%, and 50%:50% lindur flour with tapioca. The parameters observed were test for protein content, carbohydrate content, water content, ash content, lipid content, tannin content, elasticity, and preference level. Proximate data were analyzed descriptively based on SNI 01-3819-1995 on fish meatballs quality. Based on the result catfish meatballs research test concluded that the best preference catfish meatballs that is with the addition of lindur flour of 12.5% with the average value based on the criteria of the preferred organoleptic characteristics of the appearance 7.8, aroma 7.8, texture 7.5, taste 7.9 and had an alternative value of 8.00. The average folding test score is 5, very chewy. Result of proximate analysis showed carbohydrate result of 22.70%, protein of 14.56%, lipid content of 9.97%, ash content of 2.71%, water content of 48.93%, tannin of 6.54 ppm